Pemanfaatan Singkong Menjadi Keripik bagi Pemuda Desa Tamaran Kecamatan Hinai Kabupaten Langkat - Nanang Putra; Sahril Sandika; Samsul Hakim (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2023)
The aim of the service activity is to use cassava to make chips for the youth of Tamaran Village, Hinai District, Langkat Regency. The methods used in service activities include: 1) the service implementation team together with partners invites the entire community at a deliberation at the Tamaran Village Office to be more creative in processing cassava into chips which are then given the name